Gestão da inovação do modelo de negócios e desempenho inovador e sustentável - Frizzo, Kamila (2018)
Innovation is the driving force behind the development of organizations as they are contextualized in a dynamic and competitive market and depend on the creation of new ideas that result in competitive advantages. In order to accomplish that, several innovative strategies have been adopted by companies, such as open innovation (OI), which consists of opening up research and development (R&D) processes. This innovation model, besides enabling organizations to introduce a number of external assets, such as ideas, technologies, innovations and individuals in order to complement internal knowledge and achieve greater innovative performance, allows the export of internally generated technology to market. Therefore, the present study aimed to analyze OI management practices and their association with the business model and the sustainable and innovation performance of Brazilian industrial companies. While OI management was analyzed based on the study by Gomes (2007), business model was investigated according to studies by Kneipp (2016), Taran, Boer and Lindgren (2015), Boons and Lüdeke-Freund (2013), Kiron et al. (2013) and Osterwalder and Pigneur (2011), as well as innovation performance was evaluated from the dimensions proposed by Gunday et al. (2011) and the Organization for Economic Co-operation and Development (OECD) (2005). In turn, sustainable performance was measured from the Global Reporting Initiative (GRI) (2015). Therefore, this qualitative and exploratory research was conducted through a multiple case study with three industrial companies focused on education and health, paper and cellulose and chemical sectors. Results show that the level of structuring in external sources management of technological information varies according to the need and the specific demand of each company. In relation to the business model, it was evidenced that innovation, interaction with external agents and sustainability constitute the value proposition of companies. Findings also suggest that starting from the connectivity with external sources and meeting the sustainable criteria, companies achieve innovation performance through the development of new products and processes and some specific marketing and organizational actions, as well as the sustainable performance. Based on such results, it is possible to confirm the assumption that OI management practices are associated to the business model and innovation and sustainable performance in Brazilian industrial companies.